Cyclic behaviour of bearing-type bolted connections with slot bolt holes. Issue 3 (February 2019) - Li, Guo-qiang; Hou, Zhao-xin; Sun, Ying-zhi; Gong, Chao; Jiang, Jian
This article experimentally studies the behaviour of high-strength bolted connections with slot bolt holes under cyclic load to evaluate its seismic performance. A total of six specimens varying in the bolt diameters and pretension are designed and tested. The results show the connections with slot holes have good energy dissipation capacity. It is found that connections with M30 bolts, of which the hysteretic loops are fuller, have better energy dissipation capacity than that of M20 bolts connections. With the increase of number of loading cycles, the sliding force of the connections decreases. On the other hand, the ultimate bearing capacity of the connections does not decrease much both for M30 and M20 bolts. As the experiments proceed, the friction coefficients and the areas of the hysteresis curves decrease in a similar trend because of the smoothing of surfaces. The experimental results indicate the potential application of the connections with slot bolt holes as dual-function parts in structures to simultaneously provide stiffness and energy dissipation capacity.